THE SPATIAL DISTRIBUTION OF NITROGEN DIOXIDE IN ATMOSPLERIC SURFACE LAYER OF ALMATY CITY: THE SPATIAL DISTRIBUTION OF NITROGEN DIOXIDE IN ATMOSPLERIC SURFACE LAYER OF ALMATY CITY - Almira, Daulbayeva; Dinara, Zhetpisbay; Filipova, Margarita (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The level of air pollution by nitrogen dioxide in Almaty city has been monitored over the past five years (2009 - 2013). The distribution characteristics of impurities’ concentrations in the air basin of urbanized area are reviewed with regard to space and time. It’s been revealed that the level of city’s air pollution varies depending on the season.